Caracterização e desempenho econômico dos sistemas de produção de ovinos Morada Nova no estado do Ceará - Sousa Neto, Jaime Martins de (2011)
This chapter has the aim to make the technical analysis of production systems in Morada Nova sheep to complement the project "Characterization and basis for the genetic improvement of sheep Morada Nova", coordinated by Embrapa Goats and Sheep, with the financial support of Banco do Nordeste (FUNDECI / ETENE). In order to achieve this objective, primary research was conducted with data collected through the application of questionnaires to the sheep farmers of the municip ality of Morada Nova, Ceará State. To assess the technological level, the system of sheep was divided into four components: the producer management, infrastructure, production system, herd management and performance of the herds. Next, we determined the te chnological indices for each component separately and for all of them, based on its recommended technology. We found four production systems baptized by the technology index for each producer, being called "high technology gap" - level D, "regular technolog ical gap" - level C, "low technology gap" - level B and "high art " - level A. It was found that 17% of farmers fall in the level A, 33% at level B, Level C in 33% and 17% at level D.